Comparative Assessment of Psychophysiological Indicators Schoolchildren with Different Learning Models (Journal of Educational Sciences, 2022)
The problem of the psych emotional state of students in the learning process is of great practicalimportance in the context of studying the emotional stability of the personality. The introduction ofdistance learning, innovative computer technologies in educational practice cannot but affect the psychemotional state of students. The mental and physical health of a student is directly related to the emotional security of the educational environment. During the period of isolation, the student is influencedby a complex of factors: the family environment, increased social and emotional stress, an increase ineducational and computer load, an increase in responsibility for doing homework, which affects the behavioral sphere. In order to study the peculiarities of the psych emotional state of the study, participated116 students of the school № 42 of Almaty city were surveyed by the method of questioning during thedistance and traditional formats of education, as well as with a self-assessment of the state of health.The results of the study expand the scientific understanding of the psych emotional states of students,contribute to the improvement of methods for their regulation, can be used to develop programs forpsychoprophylaxis, psych correction and psychological and pedagogical support of schoolchildren whoare forced to be in self-isolation in connection with the transition to distance learning.Key words: educational environment, psychoemotional state, psychophysiology, adaptation,schoolchildren.